Natural Feeding and Description of Clausocalanus furcatus Order Calanoida (Copepoda) in the coastal waters of Baniyas City (Eastern Mediterranean) - Mayya, Wassim Mahmoud; Al- Hanoun, Kamal Salem (Journal of agricultural, environmental and veterinary sciences, 2021)
This study, included the feeding of Clausocalanus furcatus of crustacean zooplankton (Calanoida), by studying the structure of the mandible and the gut content of this previous species to determine their favorite food. 93 samples have been collected vertically in period between March and October 2020. The samples were also accompanied with different hydrophysical and hydrochemical measurements in three regions that differ from each other with their environmental properties. The number of members of (C.furcatus) that were studied reached (64) individuals, of which (44) are female and (20) are male. On the other hand, determining the morphology, studying its structure, and knowing the content of the gut of the aforementioned species helped in expanding knowledge about the conditions and strategies of feeding it under the influence of environmental factors. The number of algae species (phytoplankton) that C.furcatus fed reached (9) species, of which (6) belong to the Dinophyceae, (2) species to Bacillariophyceae earth, and (1) only one species to the group Cryptophyceae. The highest average number of Dinophyceae was (1755), followed by Bacillariophyceae (505) individuals, then the group of Cryptophyceae (189) individuals.